USPSTF Testicular Examination Nomination–Self-Examinations and Examinations in a Clinical Setting. Issue 5 (September 2018) - Fadich, Ana; Giorgianni, Salvatore J.; Rovito, Michael J.; Pecchia, Gregory A.; Bonhomme, Jean J.; Adams, Wesley B.; Stephenson, Colin L.; Mesa-Morales, Felipe E.; Sparkes, Justin Scott
In 2004, the U.S. Preventive Services Task Force (USPSTF) published a Grade D recommendation for both testicular self-examination (TSE) and clinical evaluation to screen for testicular cancer in asymptomatic males. This review committee reaffirmed these recommendations in 2009 and again in 2011 (Testicular Cancer: Screening Release Date: April 2011. Final Update Summary: Testicular Cancer: Screening. U.S. Preventive Services Task Force. September 2016). The 2011 USPSTF review found no significant evidence that would warrant a change from the last full review in 2004. We believe that the USPSTF erred in its assessments. As acknowledged in the task force report, testicular cancer is not believed to be preventable, and treatment of early detected testicular cancer is generally associated with very favorable outcomes; it is our belief therefore that every encouragement should be given to early detection. We are therefore requesting that the USPSTF review the D rating for testicular examination, both in a clinical setting and as self-examination. We are requesting this, as recent studies and public health warrant a change in grade. The new studies build on earlier studies that support the benefits of regular screening by individuals and their physicians. Further, and equally important, we believe that the current grade and attendant information confuses men and boys about the importance of self-care and wellness and continues to inadvertently reinforce negative cultural attitudes. We believe that adjusting the rating to a Grade B is both warranted and necessary.